1993
DOI: 10.1038/bjc.1993.210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rehydration on guaiac-based faecal occult blood testing in colorectal cancer screening

Abstract: In the present experience rehydration doesn't produce any decrease in the positive predictive value for cancer or adenomas and the increase in the positivity rate appears quite acceptable when considering the significant increase in the detection rates of cancer and adenomas.We conclude that rehydrated HO should be introduced as the standard test for screening in order to increase sensitivity for colorectal cancer and adenomas.Screening by faecal occult blood testing has been proposed to reduce colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Currently, our estimate for rehydrated FOBT in stages before the stage of clinical detection is lower than for unrehydrated FOBT. Several studies have shown that rehydration of FOBT slides increases sensitivity 10, 27-30. Rehydration of FOBT slides was mainly done in the second phase of the Minnesota trial with only follow-up screening rounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, our estimate for rehydrated FOBT in stages before the stage of clinical detection is lower than for unrehydrated FOBT. Several studies have shown that rehydration of FOBT slides increases sensitivity 10, 27-30. Rehydration of FOBT slides was mainly done in the second phase of the Minnesota trial with only follow-up screening rounds.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that rehydration of FOBT slides increases sensitivity. 10,[27][28][29][30] Rehydration of FOBT slides was mainly done in the second phase of the Minnesota trial with only follow-up screening rounds. Because the modeled detection rates in follow-up rounds, and thus in this phase, are higher than observed, the estimated sensitivity for rehydrated FOBT needed to be low to compensate.…”
Section: Discussionmentioning
confidence: 99%
“…Rehydration increases the cost of screening but increases the sensitivity of the test, 138,139 which raises the question of whether there are other tests for fecal blood that may enhance the specificity of the methodology and contain the cost of screening. Several recent studies suggest that immunologically based tests for human hemoglobin may enhance the sensitivity of FOBT.…”
Section: Classic Approach To Bowel Cancer Screeningmentioning
confidence: 99%